Internalization of Religious Character Values Through Himpunan Putusan Tarjih Muhammadiyah Learning in College Student Boarding School - Ridho, Abiyyul; Mustofa, Triono Ali (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study aims to explain how to internalize religious character values through learning Himpunan Putusan Tarjih Muhammadiyah at the KH. Mas Mansur student boarding school, Universitas Muhammadiyah Surakarta. This research utilizes a qualitative method with a phenomenological approach. The research data collection technique was performed through interviews, observation, and documentation. Data analysis was carried out based on the analysis initiated by Miles and Huberman, namely data reduction, data presentation, conclusion drawing, and verification. The data is summarized and then juxtaposed with supporting theories, discourses, and research. The research results show that five religious character values are internalized through Himpunan Putusan Tarjih learning to mahasantri: collaboration, independence, hard work, honesty, and brotherhood. The strategy of internalizing religious character values in Himpunan Putusan Tarjih uses the lecture method, demonstration method, and problem-based learning through discussion. Furthermore, some obstacles were still encountered in its implementation, namely the limited duration of learning and the lack of enthusiasm and activeness of the mahasantri in learning, so learning did not seem very conducive. The supporting aspects that influence the internalization of religious character values are the natural instincts of individuals, habits that are practiced repeatedly, and the good influence of the environment and people around them. As for the aspects that obstruct the process, namely the lack of awareness of mahasantri, the use of technology, and the lack of management supervision. Therefore, it is essential to have the role and responsibility of boarding school organizers in overcoming these challenges by developing a comprehensive understanding of religious character, criticism and suggestions for various attitudes and routines of mahasantri, intensive evaluation through an efficient approach, and the role of boarding school with surrounding people in maintaining good relations and striving to increase the success of internalization in various aspects of mahasantri life.